Epistemologi Falsifikasionisme Karl R. Popper: Relevansinya Bagi Teologi dan Pemikiran Keislaman - Asep Saepullah (Journal of Islamic Civilization, 2020)
One of the functions of the human mind is think rationally and scientifically. This creates an idea of ​​a theory of knowledge (epistemology) which is part of the philosophy of science with various schools and figures, namely rationalism, empiricism, positivism, and criticism. However, the existing schools received special attention because there were still many shortcomings in it, one of which was August Comte's positivism which was criticized by Karl R. Popper. Not stopping at criticism, Popper also offers new principles as solutions to the problems that criticizing. Through the three stages of the world, namely the physical world, the human world and its psychological processes and the world of science. According to Popper, the truth of a science is not determined through justification (verification), but through refuting the propositions established by science itself (falsification). Therefore, the author tries to explain how the relevance of Karl R. Popper's epistemology with theology and Islamic thought through a historical-philosophical approach. Through this approach, the authors conclude that all science has the possibility to be falsified, including theology and Islamic thought